2004
DOI: 10.1210/me.2004-0259
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Signaling Is Critical to Estrogen-Mediated Uterine Growth

Abstract: Major biological effects of estrogen in the uterus are thought to be primarily mediated by nuclear estrogen receptors, ERalpha and ERbeta. We show here that estrogen in an ER-independent manner rapidly up-regulates the expression of Wnt4 and Wnt5a of the Wnt family and frizzled-2 of the Wnt receptor family in the mouse uterus. One of the mechanisms by which Wnts mediate canonical signaling involves stabilization of intracellular beta-catenin. We observed that estrogen treatment prompts nuclear localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 67 publications
10
159
1
3
Order By: Relevance
“…Post-coital contraceptive potential of puerarin evidence suggests that oestrogen-mediated uterine events for implantation are primarily mediated via nuclear receptors. Oestrogen mediates its effects by two ER subtypes, ERa and ERb (Hou et al 2004). The mRNA of the two ER subtypes coexists in the rat uterus during pregnancy (Minorics et al 2004), but the process of embryo implantation possibly involves ERa-mediated endometrial effects (Ma et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-coital contraceptive potential of puerarin evidence suggests that oestrogen-mediated uterine events for implantation are primarily mediated via nuclear receptors. Oestrogen mediates its effects by two ER subtypes, ERa and ERb (Hou et al 2004). The mRNA of the two ER subtypes coexists in the rat uterus during pregnancy (Minorics et al 2004), but the process of embryo implantation possibly involves ERa-mediated endometrial effects (Ma et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Implantation is a crucial step in the process of establishment of pregnancy, and in rats and mice, it involves participation of oestrogens to a significant extent (Psychoyos 1973). The effects of oestrogens appear to be mediated by two oestrogen receptor subtypes, ERa and ERb (Hou et al 2004). The intriguing biology of oestrogens on different target cells is determined by the structure of the ligand and the ER subtype involved.…”
Section: Introductionmentioning
confidence: 99%
“…The role of ␤-catenin as a coactivator of androgen receptor has been well established in prostate cancer cells. Through their interaction, ␤-catenin augments androgen receptor (AR)-mediated transcription (29)(30)(31)(32)(33), and a functional interaction between ER ␣-and ␤-catenin has also been recently described in human colon and breast cancer cells (13) and uterus (34).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the notion that Wnt7a is derived from the embryo is consistent with previous studies. Nonetheless, canonical Wnt signaling is needed for embryoindependent, estrogen-stimulated uterine growth in the mouse (5). As is the case for implantation-associated events, these studies demonstrated that sFRP-2 blocks these responses.…”
Section: Wnts and Uterine Estrogen Responsesmentioning
confidence: 70%